Перцертивные метафоры в репрезентации концептов «ЖИЗНЬ» и «ŻУСIE» - Деева, Наталья (Acta Polono-Ruthenica, 2018)
A special role in the representation of abstract concepts belongs to the metaphor. The concept “life” in Russian and Polish languages is objectified through metaphors of perception. Metaphorically life is described through signs of color, taste, smell, tactile characteristics. The metaphors of perception, which are used as a means of representation of these concepts, are a way of expressing an emotional assessment. The similarity of a large number of metaphorical models in Russian and Polish languages says about stereotype representation by the speakers of both languages such abstract form as life.